2010
DOI: 10.1177/1024258910373874
|View full text |Cite
|
Sign up to set email alerts
|

Unions as environmental actors

Abstract: Building on a long history of concerns with the working environment, unions are now addressing issues arising from the debates and policies on the human causes of climate change. This article examines how unions are responding to such issues. Many unions are extending their capacities in relation to environmental concerns and in the process are refocusing their purpose. This is, however, not straightforward: unions are caught in a tension between pressures to ensure job creation and pressures towards environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 8 publications
2
42
0
Order By: Relevance
“…More broadly, a politicized environmental agenda — mainstreamed into their pay and reward strategies, extended deeper into non‐traditional bargaining terrain (CSR; procurement; production/working processes; product/service design) and even beyond the workplace (Snell and Fairbrother : 419–20) — may be more fruitful. As Lundstrom et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, a politicized environmental agenda — mainstreamed into their pay and reward strategies, extended deeper into non‐traditional bargaining terrain (CSR; procurement; production/working processes; product/service design) and even beyond the workplace (Snell and Fairbrother : 419–20) — may be more fruitful. As Lundstrom et al .…”
Section: Resultsmentioning
confidence: 99%
“…But although not yet a core union concern increasing numbers of British unions are becoming environmentally active (Farnhill 2016). Past research has shown some positive benefits for unions of environmental activism (Gregory et al 1999;Snell and Fairbrother 2010;TUC 2008TUC , 2010TUC , 2014 and union grey materials suggests workplace greening forms the bulk of their environmental activities. Workplace greening comprises site-or employerspecific bottom-up interventions involving union branches -ideally working in partnership with employers -conducting environmental audits to secure measurable energy savings and improvements in organizations' recycling, waste, water usage and procurement practices.…”
Section: Introductionmentioning
confidence: 99%
“…Be it in terms of reframing gender issues (Yates 2010) or climate change and environmental sustainability (Snell and Fairbrother 2010) or engagement in international alliances (Lévesque and Murray 2010a;Turnbull 2006), many studies identify capabilities such as framing as an important discriminating factor in understanding variations in union capacity. Framing also appears to be an essential ingredient in enlarging repertories of union action and contention (Fox Piven and Cloward 2000;Ganz 2004;Tarrow 2005).…”
Section: Introductionmentioning
confidence: 99%
“…according to this "radical transition" approach, to achieve the necessary carbon reductions will require an integrated and regulated energy supply, natural resources and transport systems, "socially/environmentally useful production" and "extended producer responsibility". The approach implies that, through the development of personal capabilities and occupational capacity, labour -or in Biernacki's (1995) terminology "labor power" -becomes a more active agent with real autonomy to challenge the institutional structures of VET and employment and to champion the reduction in carbon emissions, for instance in the UK through green representatives (Snell and Fairbrother 2010).…”
Section: Problems With Developing Vet For Lec In Ukmentioning
confidence: 99%